Recent Applications of Advanced Atomic Force Microscopy in Polymer Science: A Review - Nguyen-Tri, Phuong (Polymers (Basel), 2020)
Atomic force microscopy (AFM) has been extensively used for the nanoscale characterization of polymeric materials. The coupling of AFM with infrared spectroscope (AFM-IR) provides another advantage to the chemical analyses and thus helps to shed light upon the study of polymers. This paper reviews some recent progress in the application of AFM and AFM-IR in polymer science. We describe the principle of AFM-IR and the recent improvements to enhance its resolution. We also discuss the latest progress in the use of AFM-IR as a super-resolution correlated scanned-probe infrared spectroscopy for the chemical characterization of polymer materials dealing with polymer composites, polymer blends, multilayers, and biopolymers. To highlight the advantages of AFM-IR, we report several results in studying the crystallization of both miscible and immiscible blends as well as polymer aging. Finally, we demonstrate how this novel technique can be used to determine phase separation, spherulitic structure, and crystallization mechanisms at nanoscales, which has never been achieved before. The review also discusses future trends in the use of AFM-IR in polymer materials, especially in polymer thin film investigation.